Analyzing the Impact of New Rural Development Paradigm (NRDP) on Rural Development Success - Hariyanto, Asep; Saraswati; Akliyah, Lely Syiddatul; Trivaldi, Harry Nuari; Almurtadho, Ahmad Fatih (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
The goverment has implemented various policies related to rural development, for example by starting to focus development on peripheral and rural areas. With the enactment of Law No. 6 of 2014 concerning Villages, there was a shift in the development paradigm from being centralized, to decentralization, by giving freedom to regions and villages to develop their areas. The aim of the new paradigm itself is to provide a broad framework for policy makers to think about the elements that need to be considered in developing effective rural development policies. This research itself aims to measure the extent of success in rural development based on the